Comparative Study between the Overall Production Time of Digitally Versus Conventionally Produced Indirect Orthodontic Bonding Trays - Julia Plattner; Ahmed Othman; Jassin Arnold; Constantin von See (Galenos Yayinevi, 2020)
Objective:The purpose of this study was to compare the production time for indirect digitally and laboratory-produced orthodontic bonding trays.Methods:Orthodontic study casts were used in this study (n=40). The specimens were equally and randomly divided. In the digitally produced indirect bonding tray (DIBT) group (n=20), the brackets were set virtually using the Orthoanalyzer program (3Shape, Copenhagen, Denmark) to produce an indirect bonding tray that was virtually designed and 3D printed using VarseoWax® Splint material with a Varseo S 3D printer (Bego, Bremen, Germany). In the laboratory-produced indirect bonding tray (LIBT) group, the brackets were adhesively bonded to the study casts in the dental laboratory (Danube Private University, Krems, Austria), and a transfer bonding silicone tray was manufactured.Results:The t-test results showed a significant difference between the passive time during the production of DIBTs (153.8±32.8 min) and LIBTs (7 min). However, the active production time was 13.6±0.8 min for DIBTs and 17.7±1.9 min for LIBTs. Every individual process step in both groups was measured in minutes, and statistical analysis was performed.Conclusion:The total production time, including active working and passive non-working time, was higher for DIBTs than for LIBTs. However, the actual active production time for DIBTs was shorter than that for LIBTs. Within the study limitations, the digital planning and production of indirect orthodontic trays can be considered a time-efficient production method.